2022
DOI: 10.1044/2021_ajslp-21-00226
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Goals for Preschoolers With Language Difficulties and Disorders: A Scoping Review Using the International Classification of Functioning, Disability and Health Framework

Abstract: Purpose: The primary aim of this scoping review was to categorize language therapy goals reported in intervention studies for preschoolers (i.e., children from birth to 5;0 [years;months]) with language difficulties and disorders within the World Health Organization's International Classification of Functioning, Disability and Health (ICF) framework. A secondary aim was to determine whether different therapy goals were reported for two language difficulty/disorder subtypes (i.e., comparing language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 171 publications
1
6
0
Order By: Relevance
“…While clinicians are encouraged to use the ICF framework to target functional outcomes that are valued by caregivers ( McNeilly, 2018 ), the literature suggests SLPs may not be adopting that model in practice. A recent scoping review of intervention goals reported in the literature suggested most goals for preschoolers with language difficulties and disorders were categorized in the Activities component of the ICF framework and fewer goals specific to Participation were identified ( Kwok et al, 2022 ). While SLPs focus on outcomes specific to children's impairments, caregivers report prioritizing those related to Participation ( Roulstone et al, 2013 ; Thomas-Stonell et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While clinicians are encouraged to use the ICF framework to target functional outcomes that are valued by caregivers ( McNeilly, 2018 ), the literature suggests SLPs may not be adopting that model in practice. A recent scoping review of intervention goals reported in the literature suggested most goals for preschoolers with language difficulties and disorders were categorized in the Activities component of the ICF framework and fewer goals specific to Participation were identified ( Kwok et al, 2022 ). While SLPs focus on outcomes specific to children's impairments, caregivers report prioritizing those related to Participation ( Roulstone et al, 2013 ; Thomas-Stonell et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Functioning and Disability has three components: (a) Body functions and structures : physiological functions and anatomical parts of the body (e.g., production of speech sounds); (b) Activity : completing a task or action (e.g., following two-step directions); (c) Participation : involvement in various life situations (e.g., communicating with others). There are two Contextual Factors: (a) Personal Factors : an individual trait that may impact a person's disability (e.g., age, behavioral disposition, attention); (b) Environmental Factors : factors external to the individual that can influence health, well-being, and experiences (e.g., physical, social, and attitudinal environment; Kwok et al, 2022 ). Each element includes a set of codes that can be used to systematically organize reported functional outcomes in more detail ( WHO, 2001 ) and have been used for qualitative analysis in past research ( Grawburg et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, EI SLPs should collaborate with caregivers to create functional, participation-based goals that target the child's communication in natural contexts of importance to the family. Research studies for young children with communication difficulties often report activity-based outcomes (Kwok et al, 2022) which target the child's overall communication skills, raising the possibility that NDBIs do not adequately address family-centered goals. Furthermore, autistic children often experience difficulties in many domains of development and functioning (e.g., sleep, emotional and sensory regulation; (Aranbarri et al, 2021), and EI providers may need to help families gain access to information to best support children in these domains.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ultimate goal of intervention should be for children to communicate effectively in all situations that arise in their daily lives, until recently, speech and language therapy has focused almost exclusively on remediating deficits and impairments in language domains, such as morphosyntax, semantics, and phonology (Cunningham et al, 2017;Kwok et al, 2022). The assumption was that if children's language disorder was remediated, interactions in daily life would improve as well.…”
mentioning
confidence: 99%
“…The assumption was that if children's language disorder was remediated, interactions in daily life would improve as well. Currently, there is agreement among speech-language therapists (SLTs) that the focus of intervention should shift from improvement of language skills (i.e., being able to produce and decode spoken messages) to communication in daily life (Kwok et al, 2022;Singer et al, 2020). Baylor and Darling-White (2020) elucidate this in their proposal for an adjusted version of the International Classification of Functioning, Disability and Health (ICF;World Health Organization, 2001).…”
mentioning
confidence: 99%